2022
DOI: 10.1017/s1355617722000224
|View full text |Cite
|
Sign up to set email alerts
|

Pupillary response in reward processing in adults with major depressive disorder in remission

Abstract: Objective: Major depressive disorder (MDD) is associated with impaired reward processing and reward learning. The literature is inconclusive regarding whether these impairments persist after remission. The current study examined reward processing during a probabilistic learning task in individuals in remission from MDD (n = 19) and never depressed healthy controls (n = 31) matched for age and sex. The outcome measures were pupil dilation (an indirect index of noradrenergic activity and arousal) and comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“… 29 In adult participants, a similar physiological signature for outcome monitoring that differentiates pupil dilation for negative and positive outcomes was observed in healthy volunteers, but not in individuals with remitted depression. 30 These findings add to earlier 31 and more recent literature which suggests differences in physiological response to affective images, for example viewing emotional faces, in patients with current and remitted depression. 32 Taken together, our results are globally in line with the findings in healthy volunteers reported by these studies, and perhaps suggest that the experimental affective memory probe that we report in this article may have clinical utility in understanding how behavioral and physiological response to affective memories may be impaired by symptoms of depression.…”
Section: Discussionsupporting
confidence: 69%
“… 29 In adult participants, a similar physiological signature for outcome monitoring that differentiates pupil dilation for negative and positive outcomes was observed in healthy volunteers, but not in individuals with remitted depression. 30 These findings add to earlier 31 and more recent literature which suggests differences in physiological response to affective images, for example viewing emotional faces, in patients with current and remitted depression. 32 Taken together, our results are globally in line with the findings in healthy volunteers reported by these studies, and perhaps suggest that the experimental affective memory probe that we report in this article may have clinical utility in understanding how behavioral and physiological response to affective memories may be impaired by symptoms of depression.…”
Section: Discussionsupporting
confidence: 69%
“…The greater use of the ERG and the application of new protocols and analytical methods ( Mahroo, 2023 ) offers the potential to build on previous studies that have identified promising retinal biomarkers in CNS disorders ( Hébert et al, 2015 ; Demmin et al, 2018 ; Almonte et al, 2020 ; Duraković et al, 2020 ; Hébert et al, 2020 ; Silverstein and Thompson, 2020 ; Lee et al, 2022 ; Mohammad-Manjur et al, 2022 ; Silverstein et al, 2022 ; Tursini et al, 2022 ; Schwitzer et al, 2022b ). The combination of ERG functional metrics with other physiological markers such as eye-movements ( Shic et al, 2022 ), pupillary light response ( Guath et al, 2022 ), sleep patterns ( Gross et al, 2022 ) and retinal structural ( Parisi et al, 2001 ; Garcia-Martin et al, 2014 ; Kaur et al, 2015 ; Almonte et al, 2020 ; Duraković et al, 2020; Sen et al, 2020 ; Sarkar et al, 2021 ; Silverstein et al, 2021 , 2022 ; Tran et al, 2022 ) will allow clustering analyses of neurobiological and phenotypic features that may help develop new classification models and a better understanding of disease progress ( Liang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cognitive disorders typically demonstrate altered pupil responses [ 25 , 26 ] and oculomotor deficits [ 26 , 27 , 28 , 29 , 30 , 31 ]. Ample evidence shows that modulation in pupil size manifest cognitive processing and likely reflects the functioning of the locus coeruleus [ 32 , 33 , 34 ], which is a key structure in attentional processing.…”
Section: Introductionmentioning
confidence: 99%